Advantages and disadvantages of local government reform in Ukraine and foreign countries: a comparative legal analysis - Kаliuzhnyj, Rostyslav А. (P.A. Persona e Amministrazione, 2022)
A difficult political and economic situation in Ukraine in 2014-2015 is primarily attributed to the temporary occupation of Crimea and the ongoing war on the temporarily occupied territory of Donbass. Therefore, the decentralization of power and the reform of local self-government were extremely necessary to preserve and strengthen Ukrainian statehood through the introduction of new regional policies. The purpose of the article is a comprehensive analysis of the local self-government reform in Ukraine and foreign countries to determine its main advantages and disadvantages. During the research, it was found out that decentralization in the country leads to democratic transformations of the society based on the citizens’ initiative and responsibility as well as provides a decent standard of living and quality services at the local level. The introduction of decentralization can be observed in almost all areas such as administrative, political, financial, social. It significantly affects the population potential and increases the responsibility of public authorities to the population. There is an improvement in the level of public services, regarding economic, legal, political, social and ethnic problems. Finally, the following proposals were made to introduce changes in the local self-government: the rights and responsibilities should be divided between different levels of government to equalize their interests and to facilitate the development of amalgamated territorial communities. Such administrative-territorial reform will help preserve the integrity and inviolability of the state sovereignty.